Teaching benefit-cost analysis tools of the trade - Farrow, Scott (Cheltenham, UK Edward Elgar Publishing, 2018)
Teaching Benefit-Cost Analysis is a unique look at the insights of internationally recognized teachers, researchers and practitioners addressing a difficult and controversial subject. Each chapter presents a self-contained module that includes guidance to additional resources, and many contain class exercises to provide detail and inspiration that extends beyond the scope of standard textbooks. The social evaluation of public investments by governments, international organizations and non-profits is an expanding field that encompasses both new and established areas of social policy. This book expands on the methods and issues central to the study of benefit-cost analysis, with specific topics including risk, societal distribution of impacts, limited versus national effects, the statistical value of a life and more. This book's focus on classroom engagement makes it a valuable resource for teachers of benefit-cost analysis. Its attention to foundational and advanced concepts will be of interest to undergraduate or Master's-level students of public policy, economics and related areas, as well as professional economists who apply benefit-cost analysis in their work.
Includes bibliographical references and index
Keywords: Cost effectiveness -- Study and teaching (Higher); Social policy -- Economic aspects -- Study and teaching (Higher)